Understanding financial literacy factors among Gen Z in Palembang city - Leriva, Ratu Tenny; Helmi, Sulaiman; Isnawijayani, Isnawijayani; Trisninawati, Trisninawati (SEAN Institute, 2024)
This study aims to analyze the factors influencing financial literacy among Generation Z in Palembang. The research methodology employed is quantitative, assessing the strength of the relationship between dependent and independent variables within the population. A sample of 120 respondents was selected, and data were analyzed using Smart PLS 3.0 software. The analysis reveals that financial behavior and financial attitudes significantly influence financial literacy, whereas financial knowledge does not exhibit a significant influence. The overall regression model demonstrates that financial behavior, financial knowledge, and financial attitude collectively contribute significantly to explaining variations in financial literacy. However, the study is constrained by limitations in sample coverage and data collection methods. Nevertheless, the results of the simultaneous test indicate that the overall regression model is significant in elucidating the relationship between the variables under study and financial literacy. The implication of this research underscores the necessity for enhancing financial behavior and attitudes to bolster financial literacy among Generation Z in Palembang.